THE ROLE OF GOOD GOVERNANCE IN THE DEVELOPMENT - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Governance has to do with the manner in which responsibility is discharged. Such a responsibility may be acquired through election, appointment, or delegation in the public domain, or in the area of commerce (i.e.,corporate governance) (Mbaku& Smith, 2012). Therefore, good governance is taken here to mean condition whereby such responsibility is discharged in an effective, transparent, and accountable manner, while bad governance is associated with maladministration in the discharge of responsibility (Mbaku& Smith, 2012). Good governance entails the existence of efficient and accountable institutions—political, judicial, administrative, economic, corporate andentrenched rules that promote development, protect human rights, respect the rule of law, and ensure that people are free to participate in,and be heard on, decisions that affect their lives (Brinkerhoff & Derick, 2008).